-3(9-y)=-5(y-9)

Simple and best practice solution for -3(9-y)=-5(y-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(9-y)=-5(y-9) equation:



-3(9-y)=-5(y-9)
We move all terms to the left:
-3(9-y)-(-5(y-9))=0
We add all the numbers together, and all the variables
-3(-1y+9)-(-5(y-9))=0
We multiply parentheses
3y-(-5(y-9))-27=0
We calculate terms in parentheses: -(-5(y-9)), so:
-5(y-9)
We multiply parentheses
-5y+45
Back to the equation:
-(-5y+45)
We get rid of parentheses
3y+5y-45-27=0
We add all the numbers together, and all the variables
8y-72=0
We move all terms containing y to the left, all other terms to the right
8y=72
y=72/8
y=9

See similar equations:

| (8x-30)/5=4x | | 1/3(9×x+2)=4+2/3(6x+4) | | .3 | | 55x+15=9x+6 | | (5x+1)/3=21 | | x2-8x=6 | | 9t2−4t+1=5t^2 | | x2-4x=0 | | 1/2+6=13-a | | 2r+7(r=9) | | -3.7x/1.7=-37 | | 4.5x/0.60=23 | | 10x+4=4x-26 | | 4x-4=-x+36 | | 4.53=n | | 1.6/x=2.4 | | 320/x=0.4 | | 0.3x+x÷2=0.15+2 | | 0.3x=108 | | 55–4(y–5)=20 | | a+43=-12 | | 10x+4=5x+20 | | 5÷(3x-1)=12 | | 7p/3=5 | | 8-(-5n+8)=-16 | | (1+0.1-y)+y=1.1 | | P=15x2+600x+60 | | 2x+7=8x-2+65 | | 9x+3−6x=6 | | 170+(x-10)+(2x+50)=360 | | x+2x+4(2x)+((3(4(2x))=280 | | 7x+67=3x+75 |

Equations solver categories